2020
DOI: 10.1177/2325967119898118
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Response of Extracorporeal Shock Wave Therapy for Insertional Achilles Tendinopathy Between Sports-Active and Nonsports-Active Patients With 5-Year Follow-up

Abstract: Background: Insertional Achilles tendinopathy (IAT) is a common cause of posterior heel pain. Extracorporeal shock wave therapy (ESWT) has proven to be an effective treatment, but the relationship between therapeutic responses and sports activity levels has not been studied. Purpose: To compare the clinical outcomes of ESWT used to treat IATs between sports-active and nonsports-active patients over 5 years. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective study was conducted on 33 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…The search of PubMed, Embase, Web of Science database, and additional search finally yielded 470 records after duplicates were removed. The studies were screened by reviewing abstracts and full-texts according to the inclusion and exclusion criteria, and 23 studies [ 6 , 11 32 ] (containing 35 groups) were eligible for the final review, including 11 comparative studies (6 RCTs, 5 non-randomized comparative studies) and 12 non-comparative studies. The studies were published from 2003 to 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search of PubMed, Embase, Web of Science database, and additional search finally yielded 470 records after duplicates were removed. The studies were screened by reviewing abstracts and full-texts according to the inclusion and exclusion criteria, and 23 studies [ 6 , 11 32 ] (containing 35 groups) were eligible for the final review, including 11 comparative studies (6 RCTs, 5 non-randomized comparative studies) and 12 non-comparative studies. The studies were published from 2003 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Erroi et al demonstrated that both ESWT and PRP therapy were effective and safe, and there were no significant differences between two groups in VAS, VISA-A, or satisfaction rate [ 27 ]. Zhang et al showed that patients with IAT who had greater sports activity levels had better therapeutic responses to ESWT than nonsports-active patients after a 5-year follow-up [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined terminology 7 ( Chazan, 1998;Den Hartog, 2009;Fredericson, 1996;Nichols, 1989;Scott, Huisman & Khan, 2011;Wang et al, 2012) Tendinopathy location Insertional 21 (Aldridge, 2004;Benazzo, Todesca & Ceciliani, 1997;Benito, 2016;Cheng, Zhang & Cai, 2016;Chimenti et al, 2016;Chimenti et al, 2017;Den Hartog, 2009;Irwin, 2010;Maffulli et al, 2019;Mansur et al, 2019;Mansur et al, 2017;McCormack et al, 2015;Stenson et al, 2018;Thomas et al, 2010;Wei et al, 2017;Xu et al, 2019;Zellers et al, 2019;Zhang et al, 2020;…”
Section: Referencesmentioning
confidence: 99%
“…Of the included cohort studies, 21 were prospective cohort studies (Cheng, Zhang & Cai, 2016;Chester et al, 2008;Crill, Berlet & Hyer, 2014;Duthon et al, 2011;Jowett, Richmond & Bedi, 2018;Karjalainen et al, 2000;Khan et al, 2003;Knobloch et al, 2008;Mansur et al, 2019;McCormack et al, 2015;O'Neill et al, 2019;Oloff et al, 2015;Paavola et al, 2000;Silbernagel et al, 2007;Syvertson et al, 2017;Zhuang et al, 2019) and 10 were retrospective cohort studies (Alfredson & Spang, 2018;Barge-Caballero et al, 2008;Florit et al, 2019;Murawski et al, 2014;Stenson et al, 2018;Von Wehren et al, 2019; Wei et al, 2017;Zellers et al, 2019;Zhang et al, 2020). Midportion Achilles tendinopathy was investigated in 15 studies (Chester et al, 2008;Crill, Berlet & Hyer, 2014;Duthon et al, 2011;Jowett, Richmond & Bedi, 2018;Knobloch et al, 2008;Lakshmanan & O'Doherty, 2004;Murawski et al, 2014;O'Neill et al, 2019;Paavola et al, 2000;Silbernagel et al, 2007;Syvertson et al, 2017;Von Wehren et al, 2019), insertional tendinopathy was investigated in eight studies …”
Section: Cohort Studiesmentioning
confidence: 99%